Short Communication: Abundance of corn planthopper (Stenocranus pacificus Kirkaldy 1907, Hemiptera: Delphacidae) on five new corn varieties - MY SYAHRAWATI; NOVRI NELLY; HASMIANDY HAMID; SISKA EFENDI (Biodiversitas Journal of Biological Diversity, 2018)
Syahrawati M, Nelly N, Hamid H, Efendi S. 2018. Short Communication: Abundance of corn planthopper (Stenocranus pacificus Kirkaldy 1907, Hemiptera: Delphacidae) on five new corn varieties. Biodiversitas 19: 1029-1034. Both local and hybrid corn varieties have been attacked by Stenocranus pacificus or corn planthopper frequently grown in West Sumatra. So, the basic aim of the study is to know about the abundance of S. pacificus on major five corn varieties that will be intermittently released viz., N35, N37, NT10, NT104, and NT105. The study was conducted around palm plantation in Dharmasraya District using Randomized Block Design in 5 replications. The observations were made at weekly intervals throughout the season after planting up to 8 weeks. Number of S. pacificus were collected from 16 hills by using simple aspirator, selected randomly from each unit. The measurement of leaf length, leaf width, stem diameter and trichome length were also performed to confirm the physical effect of S. pacificus preferences. LSD test at 5% level of significance was done to determine the influence of different varieties on insect population. The S. pacificus preferably effect to NT10 variety as compared to other varieties from the early growth of corn, but the S. pacificus abundance was higher at the generative phase than the vegetative. There was a very rapid increase in its population from week to week. Physical factors of the plant, as like as trichome, affected the insect abundance.